A review on the thermomechanical properties and biodegradation behaviour of polyesters. (December 2019) - Larrañaga, Aitor; Lizundia, Erlantz
Graphical abstract: Abstract: The increasing societal concerns about the environmental impact of plastic waste, together with the depletion of petroleum resources, makes it imperative to develop environmentally friendly products that would potentially replace conventional petroleum based materials. Due to their inherent thermomechanical behaviour and biodegradability, biodegradable polyesters have shown explosive growth and underpin the global shift towards sustainability. In fact, the potential of ester groups to undergo hydrolytic chain scissions has brought biodegradable polyesters to the forefront of polymer science, both in fundamental research and industry level. Although the field of biodegradable polymers has been traditionally limited to aliphatic polyesters, recently, the introduction of aromatic rings into the polymer structure has allowed obtaining aliphatic/aromatic polyesters with much broader thermal, mechanical and biodegradation properties. The discovery of new synthetic approaches has boosted the development of novel biodegradable polyesters, with reported properties equivalent or even superior to conventional polymers. As polymer chemistry is a property driven science, the thermomechanical properties are often the most relevant aspects that determine product performance specifications and play a pivotal role towards the definition of the specific end-use applications of polymeric materials. Coupled with an understanding of polymer biodegradability, including hydrolytic and enzymatic degradation behaviour, the stage is set for a broadening impact of these systems on global sustainable polymer challenges. Accordingly, this review establishes an up-to-date state-of-the-art in the field of biodegradable polyesters, thoroughly analyzing and comparing their thermal, mechanical and biodegradation properties.